2014
DOI: 10.1093/icvts/ivu064
|View full text |Cite
|
Sign up to set email alerts
|

Surgical results of reoperative tricuspid surgery: analysis from the Japan Cardiovascular Surgery Database

Abstract: Surgical outcomes following reoperative tricuspid surgery were unsatisfactory. Although TVR is a last resort for non-repairable tricuspid lesions, it carries a significant risk of surgical mortality. Improving the patient's preoperative status and opting for TVP over TVR is necessary to improve the results of reoperative tricuspid surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…We agree with Pfannmuller's opinion, and we also routinely use biological prostheses, regardless of a patient's age, even in patients with a previously implanted mechanical valve (regardless of whether it is in the aortic or mitral position, or both) to avoid trouble due to endocardial temporary pacing lead implantation and excessive anticoagulation mandatory for a mechanical prosthesis in a tricuspid position [25]. While some researchers reported that tricuspid valve replacement was always associated with significantly higher mortality [1,16], others found no statistically significant differences in early and late outcomes between the isolated tricuspid valve repair and replacement surgeries [6]. However, one study reported a reduced mortality with the replacement surgery, which is in accordance with our results [3].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…We agree with Pfannmuller's opinion, and we also routinely use biological prostheses, regardless of a patient's age, even in patients with a previously implanted mechanical valve (regardless of whether it is in the aortic or mitral position, or both) to avoid trouble due to endocardial temporary pacing lead implantation and excessive anticoagulation mandatory for a mechanical prosthesis in a tricuspid position [25]. While some researchers reported that tricuspid valve replacement was always associated with significantly higher mortality [1,16], others found no statistically significant differences in early and late outcomes between the isolated tricuspid valve repair and replacement surgeries [6]. However, one study reported a reduced mortality with the replacement surgery, which is in accordance with our results [3].…”
Section: Discussionsupporting
confidence: 68%
“…Tricuspid valve disease has always been considered less clinically important than mitral and aortic valve pathology, and its optimal timing for surgical intervention remains controversial [1]. Many patients undergo concomitant tricuspid valve surgery at the time of mitral or aortic valve intervention, while isolated tricuspid valve surgery is rarely performed [2].…”
Section: Introductionmentioning
confidence: 99%
“…According to guidelines and other series 1,43 our analysis showed that age, mycotic TVIE, IVDU, reoperation for an infected prosthetic valve, and presence of right intracardiac device are negative predictors of an unfavorable outcome.…”
Section: Discussionmentioning
confidence: 77%
“…Pfannmuller's opinion, and we also routinely use biological prostheses regardless of patient age, even in patients with a previously implanted mechanical valve (regardless of whether it is in an aortic or mitral position, or both) to avoid trouble for endocardial temporary pacing lead implantation and excessive anticoagulation, which is mandatory with a mechanical prosthesis in a tricuspid position [25]. Some researchers reported tricuspid valve replacement was always associated with significant higher mortality [1,16]. Some researchers reported there were no statistical differences in early and late outcomes between the isolated tricuspid valve repair versus replacement surgery [6].…”
Section: Discussionmentioning
confidence: 99%
“…Tricuspid valvular disease has been always considered less clinically important than mitral and aortic valves pathology, and its optimal timing of surgical intervention remains controversial [1]. Many patients undergo concomitant tricuspid valve surgery at the time of mitral or aortic valve intervention, while isolated tricuspid valve surgery is rarely performed [2].…”
Section: Introductionmentioning
confidence: 99%